HUBUNGAN HIPERTENSI IBU HAMIL DENGAN BERAT BADAN BAYI BARU LAHIR DI RS DKT SIDOARJO TAHUN 2013 - Dyah Permata Sari (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2015)
One of the important causes of maternal morbiditas and mortalitas and fetus or neonatus is hypertension on pregnancy. Many factor that related with the hypertension of pregnancy, as age, history of abortion, gravida, social economy, decline etc.The purpose of this research is to identify the relations of hypertension from pregnant women with new born baby’s weight in RS DKT Sidoarjo The 2013. The type of researh used correlation analytic. The design is Cross Sectional. The independent variable is pregnant women hypertension, the dependent variable is new born baby’s weight. The Population is all women who give birth in RS DKT Sidoarjo in the 2013 as much 3906 respondent. The technique of sampling that is used on this research is probability sampling type sampling of simple random sampling procuring 363 respondent. Data was conducted by using checklist. The data will be proceed by editing, coding, data entry, scoring, tabulating. The result of this research show 363 respondent, most of the respondent are not hypertension as much 309 respondent (85,1%) and most of the new born baby’s weight are normal as much 338 (93,1%). The Data analysis used fisher exact test, the result showed with significance = 0,78 whereas α = 0,05. Through this result H0 is accepted.There is not relations between hypertension of pregnant women with new born baby’s weight, ofthe results ofthis study indicate the success of the above methods midwife or obstetrician that have been implemented. The method has been used by the Hospitalin order to early detect and deal with complications in pregnancy need to be maintained. As the advice for pregnant women checked her pregnancy in periodikly in order to know indication of pregnancy hypertension earlier, also it preventable earlier.